Pelvic Mapping: the importance of monitoring nervous system structures in the context of deep intestinal endometriosis (Research, Society and Development, 2022)
Introduction: Deep infiltrative endometriosis (PPE) is defined as the presence of stroma and endometrial glands outside the uterine cavity, requiring a surgical approach in some cases. In this context, pelvic neuromonitoring has been used in surgeries for the treatment of EPI, in addition to being suitable for various surgical procedures. Objectives: The present study aims to describe the importance of monitoring nervous system structures in endometriosis. Methods: This is a literature review based on scientific articles indexed in SCIELO, Pubmed and VHL published between 2015 and 2022. Results: Pelvic neuromonitoring enables intraoperative control of nerve functions and can thus reduce the occurrence of damage and contribute significantly to maintain the quality of life of patients. In the small pelvis, the structures of the autonomic nervous system are complex and sometimes difficult to differentiate, which makes pelvic mapping very important in this area. The system is available for use in open surgery, laparoscopic and robotic surgery. Conclusion: Therefore, neuromonitoring has become a great ally in current pelvic surgeries in which it is desired to save the autonomic neural function, as complications, making the procedure more peaceful and safer.